Kontribusi Ilmuwan Indonesia terhadap Psikologi Global: Studi Bibliometrik - Siaputra, Ide Bagus; Abraham, Juneman; Ho, Yuh-Shan (ANIMA Indonesian Psychological Journal, 2024)
This bibliometric analysis explores the contributions of Indonesian scholars to global psychology research, providing a comprehensive overview of its growth, trends, and impact in journals indexed in the Social Science Citation Index (SSCI) and Science Citation Index Expanded (SCIE). A systematic search of scholarly databases from 1992 to 2023 identified 1,174 documents, including 717 articles with at least one Indonesian author. The analysis covers various indicators: (1) publication types; (2) article and citation count; (3) journal categories; as well as (4) collaborative countries and institutional contributions. Results show that articles are the dominant publication type, with data papers having the highest citation impact. Research output has significantly increased since 2010, peaking at 147 articles in 2022. The citation histories of the top ten most-cited articles reveal varying degrees of impact over time. Multidisciplinary psychology and social psychology are the most published categories. International collaboration plays a vital role, with 81% of articles involving partnerships, particularly with the United States of America (USA). Universitas Indonesia emerges as the most productive state university, while Universitas Bina Nusantara as the most productive private university. While the increase in publications is noteworthy, the situation requires a more nuanced and contextual discussion. The interplay between publication quantity, research quality, and the broader research landscape warrants a deeper examination and wise interpretation. Analyzing titles, abstracts, author keywords, and Keywords Plus uncovers research strengths and enhances our understanding of research trends, collaboration patterns, and publication influence.